Эволюция социальной структуры: перспектива поколений - Заборовский, В. (Социология: теория, методы, маркетинг, 2005)
The article is based on data collection within “The Poles” project. It examines the 2000
social status of respondents in the context of their pretransition (1988) position. In
this way winnerslosers of transition perspective is employed. Special emphasis is
given to the generational dimension: depending on an issue studied, an analysis is
carried out within six or seven agecohorts. The major dependent variable measures
current social position on fivepoint scale: losers; nonlosers; nonwinners; winners;
and superwinners of transformation. Results show a significant role of ascribed
status: both agecohorts (generations) and parental social capital determine status
achievements during transformations. On the other hand, the author argues that
inflow into superwinners category was quite egalitarian: more or less a half of the
highest positions in 2000 (super winners) was taken by those, who in 1988 were
located on medium or lower levels of stratification ladder.